A v Switzerland: Application no 60342/16: European Court of Human Rights (Third Section): Jäderblom, President, Lubarda, Keller, Pastor Vilanova, Poláčková, Serghides, Schukking JJ: 19 December 2017. (16th May 2018) - Unknown
ABSTRACT: Human rights – Right to life – Freedom from inhuman and degrading treatment – Interference with – Applicant Iranian national claiming asylum in Switzerland – Asylum claim based on political activities in Iran resulting in alleged torture and detention – Claim rejected as asylum authorities finding that allegations not credible – Applicant seeking reconsideration of asylum claim application – Also seeking temporary admission on grounds including conversion to Christianity while in Switzerland – Arguing that conversion to Christianity giving rise to risk of ill-treatment if returned to Iran – Claim rejected on grounds that conversion to Christianity would not expose him to real risk of ill-treatment unless he had proselytized or attracted public attention to his faith – Appeal to Federal Administrative Court dismissed as ill-founded on ground that conversion only presented a risk where an individual had manifested their Christian faith in such a way as to make it visible to the outside world – Court finding no indication that Iranian authorities were aware of applicant's conversion – Applicant making application for temporary admission based on conversion and participation in a demonstration in Switzerland against the persecution of Christians by Iranian authorities – Claim rejected since mere participation in a demonstration against Iranian Government insufficient for applicant to be perceived as concrete threat by Iranian authorities – Asylum authorities finding no indications of Iranian authorities having taken any measures against applicant – Appeal to Federal Administrative Court dismissed as manifestly ill-founded – Whether applicant's deportation to Iran would constitute violation of right to life and protection against ill-treatment – European Convention on Human Rights, arts 2 and 3